REMOÇÃO DE FERRO E MANGANÊS ATRAVÉS DE FILTRAÇÃO ADSORTIVA EM ZEÓLITAS, EM ESCALA DE BANCADA E UNIDADE DE FILTRAÇÃO PILOTO - SILVEIRA, HENRIQUE AZEVEDO (2017)
The research consisted in the evaluation of the removal of iron and manganese by Adsorptive Filtration in zeolites. Laboratory bench scale trials were carried out using water from the Irati-PR region, with previous addition of iron and manganese, in two concentration conditions, 1,6 mg.L-1 and 1,0 mg.L-1 for iron and manganese, respectively; And at a second time, 3,2 mg.L-1 and 2,0 mg.L-1. Coagulation diagrams were previously prepared using Polyaluminium Chloride (PAC), aiming at the choice of the optimal operating condition for the coagulation pH x coagulant dosage. Comparative tests were also carried out on a bench with sand and anthracite coal, whose treatment was in complete cycle. A pilot-scale filtration step was developed in a rapid double gravity filter, composed of sand and zeolites, in which groundwater was treated from wells in the municipalities of Sengés-PR and Lajeado-PR. The optimal condition obtained from the coagulation diagrams was pH of 7,0 and dosage of coagulant PAC of 10 mg.L-1. In the bench filtration tests, for the initial concentrations of 1,6 mg.L-1 and 1,0 mg.L-1, sand bed, anthracite coal, zeolite without oxidation and zeolite with oxidation were respectively obtained, 65%, 81,11%, 100% and 100% for iron and 4,17%, -154,17% (increased concentration in the filtered water), 87,96% and 75% for manganese; For the initial concentrations of 3,2 mg.L-1 and 2,0 mg.L-1, average removals were 56,55%, 100%, 96,67% and 89,68% for iron, and 9,06%, -32,35% (increase of concentration in the filtered water), 94,44% and 77,78% for manganese; These results mean that the iron removal occurred well in all the beds, while the manganese was removed only in the zeolite, being better in the case where no previous oxidation with chlorine occurred; In the anthracite coal there was release of manganese compounds. In the pilot-scale filtration tests for the Sengés-PR water the iron was removed on average 90,3%, 79,92%, 82,54% and 100% in the four batteries, while the manganese was removed, On average, 86,64%, 93,98%, 97,60% and 97,55%; For the Lajeado-PR water, the iron was removed, on average, 100% in all the batteries, while the manganese was removed, on average, 90,34%, 80,10%, 93,27% and 58.29% on all four batteries. Pilot scale filtration tests were all performed without prior chlorination of the zeolites. The laboratory scale and pilot scale results allowed us to point out that the zeolite used without previous chlorine oxidation resulted in the average removal of iron and manganese satisfactory for small concentrations.